2002
DOI: 10.1089/089426802320282338
|View full text |Cite
|
Sign up to set email alerts
|

The Pulmonary Toxicology of Ultrafine Particles

Abstract: Ultrafine particles are a component of air pollution, derived from primary combustion sources, and so we have undertaken a programme of study on the mechanisms of lung injury caused by ultrafine particles. Ultrafine particles made of low-solubility, low-toxicity materials are more inflammogenic in the rat lung than fine respirable, particles made from the same material. Ultrafine particles can cause inflammation via processes independent of the release of transition metals, as shown by the fact that soluble pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
276
1
13

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 514 publications
(300 citation statements)
references
References 19 publications
10
276
1
13
Order By: Relevance
“…A linear relationship is indeed detectable between H 2 O 2 production and the SSA parameter (y = 15.9x + 21.5, where y = H 2 O 2 production in nmol/10 6 cells and x = particle surface in cm²; R² = 0.9, supplementary Figure 1). This is in agreement with a previous study which has shown a significant impact of nanosized SiC specific surface area on in vitro cellular responses (Pourchez et al, 2012) and also with results previously published in the literature for other particles like TiO 2 and carbon black (Oberdörster et al, 1994;Oberdorster, 2000;Oberdörster et al, 2005;Brown et al, 2001;Höhr et al, 2002;Donaldson et al, 2002;Fubini, 2007).…”
Section: Resultssupporting
confidence: 93%
“…A linear relationship is indeed detectable between H 2 O 2 production and the SSA parameter (y = 15.9x + 21.5, where y = H 2 O 2 production in nmol/10 6 cells and x = particle surface in cm²; R² = 0.9, supplementary Figure 1). This is in agreement with a previous study which has shown a significant impact of nanosized SiC specific surface area on in vitro cellular responses (Pourchez et al, 2012) and also with results previously published in the literature for other particles like TiO 2 and carbon black (Oberdörster et al, 1994;Oberdorster, 2000;Oberdörster et al, 2005;Brown et al, 2001;Höhr et al, 2002;Donaldson et al, 2002;Fubini, 2007).…”
Section: Resultssupporting
confidence: 93%
“…The photocatalytic activity and cytotoxicity of the anatase nano-TiO 2 are higher than that of the rutile form (Kakinoki et al, 2004;Sayes et al, 2006). Similarly, several studies suggested that lung inflammation and consequently cancer in rats could be induced after inhalation and intratracheal instillation of TiO 2 nanoparticles, with stronger inflammogenic activity in comparison with its micron-sized counterpart (Donaldson et al, 2002;Falck et al, 2009;Renwick et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…These epidemiological studies suggest that an increase in ambient particle concentration is related to an increase in acute morbidity and mortality (von Klot et al, 2005). Studies indicate that the decrease of particle size and the corresponding increase in relative surface area correlates with an increase in defense reaction in the lung tissue (Oberdorster, 2001;Donaldson, et al, 2002;Zhang et al, 2003;Donaldson et al, 2004a) and the inhalation of nanoparticles may cause diseases like lung cancer, fibrosis and inflammation in the lung and further worsen cardiovascular or respiratory diseases like asthma or bronchitis (Borm, 2004;Donaldson, 2004b;Stone, 2004). However, it is important to note that this lung toxicity database has been limited to studies of three types of nanoparticles: titanium dioxide, carbon black and diesel particles (Warheit, 2004).…”
Section: Introductionmentioning
confidence: 99%